The Impact And Result Of Diving Inheritance To The Daughter In Balinese Inheritance Law - Kadek Niawati (Universitas Negeri Gorontalo, 2020)
The research objective is to understand the rights of daughterin the Balinese inheritance law in Toili sub-district, Banggai district, central Sulawesi Province, and to understand the impact and result if a daughter receives an inheritance in reference to the Balinese inheritance law in Toili sub-district, Banggai district, central Sulawesi province. It is empirical legal research where the researcher collects data through observation, interview, and documentation. In confomity with the research finding, it is concluded that the impact and result of dividing inheritance to the daughter that if the daughter does sentence marriage, so that she will continue the lineal descendant of the family. On the contrary, if the inheritance is divided through musyawarah dan mufakat (deliberation for a consensus) thus the daughter lives with a responsibility to the parents and family although she is not the successor. The Balinese community thet migrates outside bali island will be forever lived with the custom by establishing a customary village that facilitates the Balinese communty during the joys and sorrows along with its predetermined awig-awig (regulation).